Inovasi Tata Kelola Keuangan Pemerintah Desa : Electronic Village Budgeting (E-Village Budgeting) untuk Menciptakan Good Governance di Kabupaten Banyuwangi - Ratih Kurnia Ramadhanny; Teguh Yuwono .; dzunuanus ghulam manar (Journal of Politic and Government Studies, 2018)
ABSTRACTSince the enactment of Regulation (UU) number 6 year 2014 about Village, each village will be given Rp. 1 billion. This village funds are prioritized for the development and empowerment of village communities. Under supervision of the use of village funds, the government of Banyuwangi through Village and Community Empowerment Office created an integrated village budgeting system by online. This system is called E-Village Budgeting (E-VB). This system is purposefully created for budget transparency, providing convenience in administrative accountability, financial control of the district level, as well as the ease of financial accountability and evaluation.This study is conducted through mixed method between quantitative and qualitative research by using observation data, interviews, documentations and questionnaires to explain in detail the real situation and use triangulation of data sources, methods and theories. Qualitative method is used to explain in detail about the innovation of village financial governance, while quantitative research method is used as supporting to explain the situation in society.Based on the study, the result shows that E-VB application system in accordance with the theory and innovation concept. This system is an innovation designed to facilitate village government's financial governance by utilizing the internet network in every village. The implementation of E-VB system has been successful with less constraints.Based on the researcher’s observation, the problem is servers are often down, especially when many village apparatus are using the E-VB application concurrently. In the future, the Government of Banyuwangi must increase the number of existing servers for the future E-VB application system can be operated more appropriately.Keywords: Innovation of Village Government Financial Governance, E-Village Budgeting